Problematizing K-12 "Best Practices" in the gulf cooperation council region. Issue 3 (7th November 2022) - Romanowski, Michael H; Alkhateeb, Hadeel; Sellami, Abdellatif
Emerging from the discourse of business in the 1960s, the concept of "best practices" has gained increasing status in education but has rarely been problematized. This essay aims to problematize the use of K-12 best practices in the Gulf Cooperation Council Region (GCC) since nowhere is the importing of best practices more evident than in the GCC region. Using Foucault's notion of problematization as the theoretical framework, this essay provides an understanding of how best practices have emerged as a solution to educational change, how these practices are legitimized, and how the use of best practices has evolved into challenges for those relying on best practices to bring about educational change. The discussion centres on five central challenges: (1) educational transfer and profit-making, (2) a false universalism, (3) leapfrogging, (4) language and discourse, and (5) the fidelity of implementation. The essay concludes by addressing the issue of using problematizing as a tool for transformative or reconstructive possibilities.